1987
DOI: 10.1002/aja.1001800407
|View full text |Cite
|
Sign up to set email alerts
|

Survival of myogenic cells in freely grafted rat rectus femoris and extensor digitorum longus muscles

Abstract: The objective of this study was to determine how long myogenic cells can survive in the central ischemic zone of early free muscle grafts in the rat. The study was conducted on free grafts of a large (rectus femoris) and a small (extensor digitorum longus) muscle. At times ranging from zero hr to five days post-grafting, the central zones were isolated, minced, and implanted under the back skin of mice. After five days the minces were removed and examined histologically for the presence of rat myotubes, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 23 publications
5
14
0
Order By: Relevance
“…In wing buds of avian embryos, migrating myogenic cells may be found in close proximity to a prepatterned vascular network (Solursh et al, 1987). In line with these observations, spatiotemporal correlations between the ingrowth of blood vessels into a formerly ischemic area and detection of cells with myogenic capacities in that area has been repeatedly reported (Phillips et al, 1987;Kardon et al, 2002). Although the lineage relationships between ECs and muscle progenitors is not firmly agreed upon in the literature, our present studies do strongly support a functional relationship.…”
Section: Discussionsupporting
confidence: 88%
“…In wing buds of avian embryos, migrating myogenic cells may be found in close proximity to a prepatterned vascular network (Solursh et al, 1987). In line with these observations, spatiotemporal correlations between the ingrowth of blood vessels into a formerly ischemic area and detection of cells with myogenic capacities in that area has been repeatedly reported (Phillips et al, 1987;Kardon et al, 2002). Although the lineage relationships between ECs and muscle progenitors is not firmly agreed upon in the literature, our present studies do strongly support a functional relationship.…”
Section: Discussionsupporting
confidence: 88%
“…Several investigators have demonstrated the crucial role of the satellite cells in the regenerative process (Schultz et al, 1988;Carlson, 1986;Bischoff, 1986). After autografting, the core region of muscle degenerates, while satellite cells surviving in the peripheral region appear to migrate centripetally to the degenerative region and differentiate, fusing into myotubes (Phillips et al, 1987;Schultz et al, 1988).…”
Section: Expression Of A-actin Mrnas I N Standard Autografted Edl Musclementioning
confidence: 99%
“…Following muscle trauma, there is abundant evidence for the direct migration of myoblasts from the necrotic area towards the periphery (Schultz et al, 1988). Later, during regeneration, they migrate back to the center, where they undergo myogenesis (Phillips et al, 1987). Localized muscle trauma apparently produces factors that stimulate chemotaxis of myoblasts from distant sites (Watt et al, 1994).…”
Section: Introductionmentioning
confidence: 99%